The Development of Waste Management: The Case Study of Maemok Municipality, Thailand - Butr-udom, Thanawit; Sattakorn, Wit; Methachayanan, Ekawit (Asian Administration and Management Review, 2019)
This research aimed to analyze the factors affecting the development of municipality waste management and the causal relationship of the factors affecting the development of waste management of Maemok Municipality, Thoen District, Lampang Province. Data were collected from 156 households participating in the waste management development project. The independent variables consisted of participatory behavior in waste management, awareness in waste management, technology choices in waste management, government regulations and enforcement, leadership and having responsible organizations. The dependent variable was the development of waste management. The instrument used to collect data was a questionnaire. Data were analyzed by mean, standard deviation and multiple regression analysis. According to the analysis using the stepwise method to analyze six independent variables influencing the development of waste management with the statistically significant level of.05, it was found that all independent variables, including participatory behavior in waste management, awareness in waste management, technology choices in waste management, government regulations and enforcement, leadership and having responsible organizations could explain the variation of waste management development at 57.50% (R2 =.331). The results also showed that there were only two independent variables that had statistically significant influence: awareness in waste management and technology choices in waste management.